Specimen Storage in Transport Medium and Detection of Group B Streptococci by Culture - Rosa-Fraile, Manuel (American Society for Microbiology, 2005)
Recovery of group B streptococci (GBS) was assessed in 1,204 vaginorectal swabs stored in Amies transport medium at 4 or 21°C for 1 to 4 days either by direct inoculation onto Granada agar (GA) or by culture in blood agar (BA) and GA after a selective broth enrichment (SBE) step. Following storage at 4°C, GBS detection in GA was not affected after 72 h by either direct inoculation or SBE; however, GBS were not detected after SBE in the BA subculture in some samples after 48 h of storage and in GA after 96 h. After storage at 21°C, loss of GBS-positive results was significant after 48 h by direct inoculation in GA and after 96 h by SBE and BA subculture; some GBS-positive samples were not detected after 24 h of storage followed by SBE and BA subculture or after 48 h of storage followed by SBE and GA subculture. Storage of swabs in transport medium, even at 4°C, produced after 24 h an underestimation of the intensity of GBS colonization in most specimens. These data indicate that viability of GBS is not fully preserved by storage of vaginorectal swabs in Amies transport medium, mainly if they are not stored under refrigeration.